Effect of exploitation system using a tapping stimulant on the production of four rubber plant clones (Hevea brasiliensis Mull-Arg.) in Bulukumba Regency. Issue 1 (October 2020) - Padjung, R; Mollah, A; Al-Ridho, M A F; Mustari, K; Ala, A; Rafiuddin,
Abstract: This study aims to determine the effect of tapping stimulants on the performance of four rubber plant clones. The study was conducted at Palangisang Estate, PT. PP London Sumatera Indonesia Tbk in Tamatto Village, Ujungloe District, Bulukumba Regency, South Sulawesi Province located at an altitude of 0-25 meters above sea level. The study was carried out from September to October 2019 as an experimental research using Nested Design consisted of two factors, rubber clones and exploitation system. Four rubber clones, PB 260, PM 10, RRIM 901, and GT1, were treated with 2.5% ethrel tapping stimulant which repeated on six trees for each clone. Latex weight and dry rubber content were measured compared to the control treatment. The results showed that the application of the tapping stimulants had a very significant effect on latex weight and dry rubber content. Highest latex weight was obtained from the application of the stimulant to GT 1 clone with 226.33 grams. However, clone PB 260 in the control treatment resulted in the highest dry rubber content (34.50%).